2015
DOI: 10.1021/acsmedchemlett.5b00226
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a Highly Selective JAK2 Inhibitor, BMS-911543, for the Treatment of Myeloproliferative Neoplasms

Abstract: JAK2 kinase inhibitors are a promising new class of agents for the treatment of myeloproliferative neoplasms and have potential for the treatment of other diseases possessing a deregulated JAK2-STAT pathway. X-ray structure and ADME guided refinement of C-4 heterocycles to address metabolic liability present in dialkylthiazole 1 led to the discovery of a clinical candidate, BMS-911543 (11), with excellent kinome selectivity, in vivo PD activity, and safety profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 21 publications
(44 reference statements)
0
17
0
Order By: Relevance
“…Molecular modeling suggested that a trajectory from a sp 2 center would more effectively traverse the opening between the P-loop and extended hinge region toward solvent. Appending the 2-methoxyethyl side chain to the scaffold through a sp 2 hybridized linker (13,14) maintained planarity with the azaindole core and further improved potency against JAK2 while preserving JAK family selectivity. Despite the improved selectivity, these compounds (12,13,14) were less potent than the methyl analogue (8).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Molecular modeling suggested that a trajectory from a sp 2 center would more effectively traverse the opening between the P-loop and extended hinge region toward solvent. Appending the 2-methoxyethyl side chain to the scaffold through a sp 2 hybridized linker (13,14) maintained planarity with the azaindole core and further improved potency against JAK2 while preserving JAK family selectivity. Despite the improved selectivity, these compounds (12,13,14) were less potent than the methyl analogue (8).…”
mentioning
confidence: 99%
“…Appending the 2-methoxyethyl side chain to the scaffold through a sp 2 hybridized linker (13,14) maintained planarity with the azaindole core and further improved potency against JAK2 while preserving JAK family selectivity. Despite the improved selectivity, these compounds (12,13,14) were less potent than the methyl analogue (8). An amide isostere, thiazole (15), improved potency and cellular activity, while retaining comparable levels of selectivity to the methoxyalkyl analogues.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…29 The incubation mixtures contained the following components: 1.1 nM JAK1/2/3, 1.5 mM peptide substrate (5-FAM-KKKKEEIYFFFG-OH for JAK2) and 30 mM ATP. Aer the incubation for 180 min, the reaction mixture was analyzed on a Caliper LabChip 3000 (Caliper LifeSciences, Hopinkton, MA, USA) by electrophoretic separation of the uorescent substrate and phosphorylated product.…”
Section: In Vitro Jak Inhibition Assaysmentioning
confidence: 99%
“…Some pyrazole‐based drugs are depicted in Figure . Pyrazole derivatives show anticancer activity due to their inhibition of various targets such as EGFR , IGF‐1R , tubulin , B‐raf , mTOR , HDAC , ALK , topoisomerase II , JAK2 , ROS 1 , among others. Hence, incorporation of the pyrazole moiety is an important synthetic strategy in rational drug development process.…”
Section: Introductionmentioning
confidence: 99%